2009
DOI: 10.2478/s11536-008-0079-x
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic shoulder assessment in Turkish amateur boxers

Abstract: AbstractThe most common injuries reported in the literature regarding the sport of boxing are to the brain, eyes, kidneys and hands. Shoulder injuries have not been fully reported in the literature until recently, as a result we aimed to present our arthroscopic findings in amateur boxers. Ten amateur boxers with complaints of pain in the shoulder region and decreased performance during sportsplay were enrolled. They were evaluated by physical examination, radiology and arthros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…A case series of Özkan et al (27) revealed different levels of chondropathy and pathologies of the glenoid labrum in 10 boxers with shoulder pain undergoing arthroscopy. Severity of intraarticular pathologies seemed to correlate with the years spent boxing.…”
Section: Limitationsmentioning
confidence: 99%
“…A case series of Özkan et al (27) revealed different levels of chondropathy and pathologies of the glenoid labrum in 10 boxers with shoulder pain undergoing arthroscopy. Severity of intraarticular pathologies seemed to correlate with the years spent boxing.…”
Section: Limitationsmentioning
confidence: 99%